2010
DOI: 10.1097/iae.0b013e3181c96a87
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Characteristics, and Causes of Vision Loss in Children With Vogt-Koyanagi-Harada Disease in South India

Abstract: Vogt-Koyanagi-Harada disease is an uncommon cause of uveitis in children. The clinical characteristics of pediatric Vogt-Koyanagi-Harada disease in South India resembled those described in cohorts from other regions. Although children in our cohort tended to do well with prompt diagnosis and treatment, long-term vision loss can occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
0
18
1
2
Order By: Relevance
“… 6 , 7 In a study from a referral eye care center in South India, the prevalence is reported as 1.4%–3.5%. 8 VKH is seen more frequently in an adult population, and women are more frequently affected. 9 VKH disease usually manifests as four distinct clinical phases: prodromal, acute uveitic, convalescent, and chronic recurrent.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 In a study from a referral eye care center in South India, the prevalence is reported as 1.4%–3.5%. 8 VKH is seen more frequently in an adult population, and women are more frequently affected. 9 VKH disease usually manifests as four distinct clinical phases: prodromal, acute uveitic, convalescent, and chronic recurrent.…”
Section: Introductionmentioning
confidence: 99%
“…Little has been reported in the literature regarding the expected course or management of the integumentary features of VKH. Most publications are ophthalmology based and treatment is discussed in the context of managing the syndrome as a whole (2,4,5). The integumentary changes may be permanent, but there is a published case series suggesting that vitiligo and poliosis may be reversible with systemic immunotherapy (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although women are more affected overall [2,3], a higher proportion of men may be affected in the Japanese population [4]. As with most types of uveitis, VKH is seen more frequently in the adult population, although the disease has been reported in children [5,6], the youngest of which was a 3-year-old girl [7].…”
Section: Epidemiologymentioning
confidence: 96%